A preliminary study on functionality of Gundelia tournefortii L. as a new stabiliser in ice cream production. (17th March 2013) - Cakmakci, Songul; Dagdemir, Elif
Abstract : The aim of this study was to investigate the effect of Gundelia tournefortii L. leaves and G. tournefortii L. milk as a new natural stabiliser on the quality characteristics of ice cream. For this aim, G. tournefortii L. leaves were added to an ice cream mix at three different concentrations (0.6, 1.0 and 3.0% w/w), and also, its milk was used as a stabiliser at 0.6% w/w concentration for ice cream production. Certain physical and sensorial characteristics of ice creams were compared with those of some commercial food gums such as guar gum, carrageenan and salep. Also, the chemical structure of G. tournefortii L. milk was determined using infrared spectra and elemental analyses. In comparison with commercial stabilisers, G. tournefortii L. did not display a notable effect on quality characteristics (viscosity, overrun, first dripping times and complete melting times). However, when considering these quality characteristics, the values for G. tournefortii L. milk were close to the values obtained for the commercial gums. In terms of sensorial characteristics, all the concentrations of G. tournefortii L. leaves were given low scores by panellists compared to the commercial stabiliser. However, G. tournefortii L. milk was given scores similar to the commercial stabiliser.